Avaliação do papel do potencial evocado miogênico vestibular cervical e eletrococleografia no diagnóstico da migrânea vestibular - Rodrigues, Talita Parente (2018)
The strong link between migraine and vertigo has been mentioned since the nineteenth century, but systematic studies of the association of these symptoms were only initiated in the following century. In the last three decades, Vestibular Migraine (VM) has taken shape as a diagnostic entity that can affect up to 1% of the population. The Cervical Vestibular Evoked Myogenic Potential (cVEMP) is an electrophysiological test used to evaluate the saccule-colic function. Electrocochleography (ECoG) is an evoked short-latency auditory potential, which allows the recording of bioelectric events of the cochlea and cochlear nerve as a result of sound stimulation. The objective of the study is to investigate the role of cVEMP and ECoG in the diagnosis of vestibular migraine. Thirteen women with clinical medical diagnosis of VM, average age of 44 years and 13 healthy volunteers, paired by gender and average age, without hearing and/or vestibular complaints for the control group were evaluated through the cVEMP and ECoG tests. The presence of vertigo and headache was mentioned by all members of the group with VM, associated with symptoms such as nausea (92.3%), photophobia (92.3%) and phonophobia (69.2%). Tinnitus was the most frequent hearing complaint (61.6%). Spontaneous nystagmus with closed eyes was present in 30% of the participants and the caloric evidence showed 40% asymmetry. A significant increase in latency of peak P1 and N1 in the test group was observed in relation to the control group. There was no significant difference in the occurrence of asymmetry and decreased amplitudes to the cVEMP. Electrocochleography evidenced increased amplitude of the sum potential and the changed PS/PA ratio was double in the group with VM. Changes in latency increase to cVEMP may suggest central injury. Patients with vestibular migraine may present electrocochleography compatible with endolymphatic hydrops. Keywords: Migraine. Vertigo. Evoked potential. Electrocochleography.